The efficacy and characteristics of warm-up and re-warm-up practices in soccer players: a systematic review - Hammami, A.; Zois, J.; Slimani, M.; Russel, M.; Bouhlel, E. (The Journal of Sports Medicine and Physical Fitness, 2018)
INTRODUCTION: This review aimed 1) to evaluate the current research that examines the efficacy of warm-up (WU) and re-warm-up (RWU) on physical performance; and 2) to highlight the WU and RWU characteristics that optimise subsequent performance in soccer players.